Efi Avdela, Haris Exertzoglou and Christos Lyrintzis, eds. Μορφές δημόσιας κοινωνικότητας στην Ελλάδα του εικοστού αιώνα [Forms of public sociality in 20th-century Greece] - Kouki, Eleni (Historein, 2018)
Efi Avdela, Haris Exertzoglou and Christos Lyrintzis, eds. Μορφές δημόσιας κοινωνικότητας στην Ελλάδα του εικοστού αιώνα [Forms of public sociality in 20th-century Greece]. Rethymno: University of Crete, 2015. 384 pp.